ANALISIS EFEKTIVITAS BIAYA (Cost Effectiveness Analysis) PENGGUNAAN ANTIPSIKOTIK MONOTERAPI ATIPIKAL DENGAN KOMBINASI ATIPIKAL DAN TIPIKAL PADA PASIEN RAWAT INAP SKIZOFRENIA DI RUMAH SAKIT JIWA GRHASIA YOGYAKARTA - Novi Afitriyani; Afitriyani, Novi Afitriyani; Dwinta, Eliza; Radne Rimba Putri, Imram; Susila Astuti, Witri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Schizophrenia is a serious mental disorder characterized by impaired thinking, hallucinations and social behavior. Yogyakarta Special Region (DIY) ranks 2nd with a prevalence of schizophrenia reaching 10.4 per 1,000 population. The high number of people suffering from mental disorders can lead to increasingly expensive costs. To reduce the problem of health financing, a cost-effectiveness analysis is needed by calculating the cost of antipsychotic drugs and calculating the Average Cost Effectiveness Ratio value. The aim of this study was to determine the cost-effectiveness of using atypical antipsychotic monotherapy with atypical and typical combinations in schizophrenia patients at RSJ Grhasia Yogyakarta. The research method was carried out descriptively and retrospectively using medical record data for the period January-December 2022, with a proportional sampling technique. Results: research shows that atypical monotherapy antipsychotics are more cost-effective with an Average Cost Effectiveness Ratio value of IDR 204.4/week of therapeutic treatment compared to atypical-typical combination antipsychotics with a greater value of IDR 343.2/week of therapeutic treatment. Conclusion: The antipsychotics used by inpatient schizophrenia patients at RSJ Grhasia Yogyakarta had the highest effectiveness, namely in the atypical monotherapy therapy group, amounting to (93.02%).